Effects of phase composition and elemental partitioning on soft magnetic properties of AlFeCoCrMn high entropy alloys. (1st June 2019) - Jung, Chanwon; Kang, Ku; Marshal, Amalraj; Pradeep, Konda Gokuldoss; Seol, Jae-Bok; Lee, Hyuck Mo; Choi, Pyuck-Pa
Abstract: We investigated the microstructure evolution, phase formation, and soft magnetic behavior of as-cast Al0.1 (Fe1+x CoCr1-x Mn)0.9 (x = 0, 0.2, 0.4, 0.6, 0.8) high entropy alloys using combined atom probe tomography, electron microscopy, and ab initio density functional theory calculations. Up to x = 0.6, the alloys consisted of a disordered BCC matrix and nano-scale ordered B2 precipitates, where for x = 0.8 a small fraction of a FCC phase (18.3 vol %) was formed. Using the structural information from electron microscopy and chemical information from atom probe tomography as inputs for density functional theory calculations, we determined the electronic density of states and magnetic moments associated with each alloying element. Fe and Co showed ferromagnetic behavior in all three phases, whereas Cr exhibited antiferromagnetic coupling with Fe and Co. Mn showed a strongly reduced net magnetic moment in FCC as compared to BCC and B2. Thus, substituting a maximum amount 13.5 at.% of Cr by Fe without forming the FCC phase, i. e. the Al0.1 (Fe1.6 CoCr0.4 Mn)0.9 alloy, resulted in the highest saturation magnetization (135 Am 2 /kg) among the alloys studied in this work. Graphical abstract: Image 1